FOREIGN EXCHANGE MANAGEMENT AND PROFITABILITY OF DEPOSIT MONEY BANKS IN NIGERIA - Adekunle Christopher, Williams,; Cecilia Adurayemi, Adu, (International Journal of Multidisciplinary Reseach, 2026)
This study investigated the effect of foreign exchange management on the profitability of Deposit Money Banks (DMBs) in Nigeria by obtaining data from five banks between 2020-2024.Regression analytical method was adopted for this study. It was found out that foreign reserves significantly and positively affected return on asset. The study concluded that foreign exchange management profoundly influenced bank profitability in Nigeria. It was recommended that there should be forex risk management and foreign reserves for strategic planning, and investing in exchange rate forecasting tools for DMBs.